The presidential elections of Trump and Bolsonaro, whiteness, and the nation - Penha-Lopes, Vânia (Lexington Books, 2022)
"The Presidential Elections of Trump and Bolsonaro, Whiteness, and the Nation is a sociological analysis of the similarities between the elections of Donald Trump and Jair Bolsonaro, based on biographies, academic sources, newspaper, television, and internet reports published in the United States and Brazil between 2014 and 2021"--